'I don't want to die, I want to feel better': finding hope through psychoanalytic parent-infant psychotherapy. Issue 3 (2nd September 2019) - Ogbuagu, Coretta
ABSTRACT: This paper follows the journey of a young black woman as she enters motherhood during treatment in psychoanalytic parent-infant psychotherapy with a black female therapist. The impact of the mother's early trauma on the developing parent-infant relationship is explored through the theme of being seen . Transference and countertransference phenomena are examined. There is a particular focus on the mother's race, sexuality and gender and their impact on her growing son. Winnicott's attention to the use of black in the consulting room is drawn upon, to open up a discussion about some of the clinical implications regarding sameness in therapist and patient, both being black and female. Finally, the practice of video-recording sessions and what this elicits in the countertransference is also explored, providing another perspective to the theme of being seen .